Construction of the Concept of Solidarity Economy: A Look at Comprehensive Economic Theory - Vélez Tamayo, Julián Mauricio (Cooperativismo & Desarrollo, 2014)
The article proposes a shift in traditional economic theory based on contributions from the field of comprehensive economic theory by Luis Razeto Migliario (1994). To do so, in addition to showing important aspects of the proposed theory, the results are given from an approach based on the experience of associativity in certain agricultural and livestock raising organizations in three municipalities in eastern Antioquia. These organizations, rather than focusing on growth of the capital factor, are strengthened through growth of the community factor by boosting the other factors (work, financial means, material means, technology and management). The research takes place in the context of the farming economy, which is examined using the Forero approach (2003), and stresses the family farming nature of theorganizations. It is clear from the characteristics of the association under study that, although they have not developed strong financial and material factors, they are held together by values that strengthen the community factor.
Keywords: farm economy; solidarity economy; C factor; economic factor; comprehensive economic theory.